Blue emissive dimethylmethylene-bridged triphenylamine derivatives appending cross-linkable groups. Issue 19 (5th May 2020) - Zhou, Kangyu; Pan, Hongfei; Zhang, Yongjie; Wang, Houchen; Dong, Xiaofei; Ren, Xiangkui; Li, Xianggao; Wang, Shirong; Chen, Zhijian
Abstract : Blue-emissive and cross-linkable dimethylmethylene-bridged triphenylamine derivatives were synthesized and their optical and electrochemical properties were investigated. Abstract : Five new dimethylmethylene-bridged triphenylamine (DTPA) derivatives 4a–e bearing peripheral cross-linkable vinyl and trifluorovinyl groups were synthesized. The chemical structure of these compounds was characterized by 1 H NMR, 13 C NMR and HRMS. Their optical properties were studied by UV/Vis spectroscopy and fluorescence spectroscopy. Based on these studies, blue-coloured fluorescence and high fluorescence quantum yields were obtained for 4a–e . The electrochemical properties of these compounds were studied by cyclic voltammetry and the results were further elucidated by DFT calculations. Furthermore, the thermotropic properties of the new DTPAs were investigated by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Compounds 4a–d exhibit high thermal stability and thermal cross-linkable properties. These results provide an effective strategy for the design and synthesis of thermally stable and cross-linkable DTPA derivatives with tunable optical and electrochemical properties.